DOMINASI DAN LEGITIMASI KEKERASAN SEKSUAL PEREMPUAN DALAM TRADISI RONJHENGAN DI MADURA - khairiyanto Matroni (JURNAL SETIA PANCASILA, 2021)
In Context of Gender, Patriarchal Cultural often was indicated to husband. Discourse of Gender more excessive discussed about it which have occurred publicly including: subordination, violence, sexual harassment for women. On the other hand, one side, the cultural too have followed to role in forming discourse of gender where role of women always is valued negative. In the case here, Ronjhengan is specially women less obtainable interest of well. Ronjhengan as cultural often put women side eliminated that women is always cornered in practice it specially about women body and other side, cultural as aspect of importing in life community Madura. in the research, cultural of Ronjhengan which is being Madura, will be studied through in perspective sort story from Ahmad Muhklish Amril further continue called Mushlish. the research analyses used theory of structuration-agent Pierre Boerdieu, continue namely Boerdieu. the context explain that (Habitus: Agen x Modal)+Ranah: Practect, Subtansi doxa as value which necessary construction or being practice of social gap for women to restore position harkat-martabat women in socity